Actual Anatomical and Dosimetric Changes of Parotid Glands in Nasopharyngeal Carcinoma Patients during Intensity Modulated Radiation Therapy. (22nd February 2015) - Ren, Gang; Xu, Shou-Ping; Du, Lei; Feng, Lin-Chun; Qu, Bao-Lin; Liu, Hai-Xia; Xie, Chuan-Bin; Ma, Lin
Abstract : The goal of this study was to evaluate the actual anatomical and dosimetric changes of parotid glands in nasopharyngeal carcinoma patients during intensity modulated radiation therapy. With helical tomotherapy, its planning system, and adaptive software, weekly anatomical and dosimetric changes of parotid glands in 35 NPC patients were evaluated. Interweekly parotid volume varied significantly (P < 0.03 ). The rate of volume change reached the highest level at the 16th fraction. The average V 1 increased by 32.2 (left) and 28.6 (right), and the average D 50 increased by 33.9 (left) and 24.93 (right), respectively. Repeat data comparison indicated that the V 1 and D 50 varied significantly among different fractions (both with P = 0.000 ). The variation of parotid volume was inversely correlated with that of the V 1 and D 50 (both with P = 0.000 ). In conclusion, parotid volume and actual dose vary significantly in NPC patients during IMRT. Replanning at the end of the fourth week of IMRT may have clinical benefits.